Inflammatory Response Mechanisms Exacerbating Hypoxemia in Coexistent Pulmonary Fibrosis and Sleep Apnea - Ayodeji Adegunsoye; Jay Balachandran (Mediators of Inflammation)
Mediators of inflammation, oxidative stress, and chemoattractants drive the hypoxemic mechanisms that accompany pulmonary fibrosis. Patients with idiopathic pulmonary fibrosis commonly have obstructive sleep apnea, which potentiates the hypoxic stimuli for oxidative stress, culminating in systemic inflammation and generalized vascular endothelial damage. Comorbidities like pulmonary hypertension, obesity, gastroesophageal reflux disease, and hypoxic pulmonary vasoconstriction contribute to chronic hypoxemia leading to the release of proinflammatory cytokines that may propagate clinical deterioration and alter the pulmonary fibrotic pathway. Tissue inhibitor of metalloproteinase (TIMP-1), interleukin- (IL-) 1α, cytokine-induced neutrophil chemoattractant (CINC-1, CINC-2α/β), lipopolysaccharide induced CXC chemokine (LIX), monokine induced by gamma interferon (MIG-1), macrophage inflammatory protein- (MIP-) 1α, MIP-3α, and nuclear factor- (NF-) κB appear to mediate disease progression. Adipocytes may induce hypoxia inducible factor (HIF) 1α production; GERD is associated with increased levels of lactate dehydrogenase (LDH), alkaline phosphatase (ALP), and tumor necrosis factor alpha (TNF-α); pulmonary artery myocytes often exhibit increased cytosolic free Ca2+. Protein kinase C (PKC) mediated upregulation of TNF-α and IL-1β also occurs in the pulmonary arteries. Increased understanding of the inflammatory mechanisms driving hypoxemia in pulmonary fibrosis and obstructive sleep apnea may potentiate the identification of appropriate therapeutic targets for developing effective therapies.